Analytical study of requirements elicitation techniques based on graphical representations - Pereira de Moraes, Reinaldo; Padovani, Stephania (InfoDesign, 2023)
This paper presents, from the Information Design perspective, an analytical study of requirements elicitation techniques based on graphical representations. The objective of this study is to investigate the features of techniques that enable the elaboration of graphical representations in the requirements elicitation process for software development. This research has an applied nature, with descriptive objectives, as it adopts the method of literature review in order to develop and apply a protocol for analyzing requirements elicitation techniques. As a result, the following are presented: (1) classification of techniques according to the characteristics analyzed by the protocol, (2) suggestion of two new patterns of information organization, and (3) expectations regarding the characteristics of a functional requirements elicitation tool based on visual artifacts that can be developed in another project.